Conflicts of supply chains in multi-channel marketing:a case from northern Finland - Rusko, Rauno Tapio (Technology Analysis & Strategic Management, 2016)
Multi-channel marketing is a popular research theme of marketing management. Studying multi-channel marketing is a popular research theme of marketing management. The studies emphasise the necessity and advantages of multi-channel marketing. Despite these advantages, multi-channel marketing is also a source of conflicts in supply chains because the coordination of supply chain ecosystem is challenging. This study is based on a questionnaire and interviews of entrepreneurs. The large significance of dealer, large turnover and the intention to bypass middlemen in the supply chain are sources of conflicts. Variables, which seem to have decreasing effects on conflicts are ‘large number of employees’, ‘intentions to sell different products via different channels’ and slightly in the case ‘to achieve competitive advantage via online shop’. Successful exploitation of e-commerce and multi-channel marketing needs intensive adaptation of entrepreneurs in each step. Each marketing channels need their own planning and sub-strategies. The strategic decisions of e-commerce are part of the whole strategy of the entrepreneurs and the firm.